Effects of defocus on the transfer function of coherence scanning interferometry - Su, Rong; Thomas, Matthew; Leach, Richard; Coupland, Jeremy (Optical Society of America, 2017)
Coherence scanning interferometry (CSI) offers three dimensional (3D) measurement of surface topography with high precision and accuracy. Defocus within the interferometric objective lens, however, is commonly present in CSI measurements, and reduces both the resolving power of the imaging system and the ability to measure tilted surfaces. This paper extends the linear theory of CSI to consider the effects of defocus on the 3D transfer function and the point spread function in an otherwise ideal CSI instrument. The results are compared with measurements of these functions in a real instrument. This work provides further evidence for the validity of the linear systems theory of CSI.